IMPLEMENTASI PEMBELAJARAN E-LEARNING BERBASIS WEBSITE UNTUK MENINGKATKAN HASIL BELAJAR DAN MOTIVASI SISWA KELAS XI IPA 1 PADA MATERI KELARUTAN DAN HASIL KALI KELARUTAN (KSP) DI SMAN 12 BANJARMASIN - Mohammad Noorsalim; Siti Halimah Nurdiniah; Parham Saadi (Universitas Lambung Mangkurat, 2014)
Abstract. Has done research about implementation e-learning study based website in science class 1 grade XI of SMAN 12 Banjarmasin. This research aims to know improved learning outcomes and student‟s motivation in solubility and solubility product material by implemented study e-learning based website. This research uses classroom action research design, with 2 cycles. Every cycles consist of stage planning, action, observation and evaluation and also analysis and reflection. The subject of research are 29 students science class 1 grade XI of SMAN 12 Banjarmasin . Data collected by online test in website and motivation questionnaire. Data analyzed by presentation technic and explained in quantitative and qualitative. The results showed that by implementation e-learning study based website can increase learning outcomes of solubility and solubility product material from cycle 1 to cycle 2. Understanding level of student increase from 85,19% in cycle 1 become 100% in cycle 2. Student motivation by implementation e-learning study based website in “very well” category.Keywords: e-leaning, website, solubility and solubility product